ANIE: A mathematical algorithm for automated indexing of planar deformation features in quartz grains - HUBER, Matthew S.; FERRIÈRE, Ludovic; LOSIAK, Anna; KOEBERL, Christian (Meteoritics & planetary science, 2011)
– Planar deformation features (PDFs) in quartz, one of the most commonly used diagnostic indicators of shock metamorphism, are planes of amorphous material that follow crystallographic orientations, and can thus be distinguished from non‐shock‐induced fractures in quartz. The process of indexing data for PDFs from universal‐stage measurements has traditionally been performed using a manual graphical method, a time‐consuming process in which errors can easily be introduced. A mathematical method and computer algorithm, which we call the Automated Numerical Index Executor (ANIE) program for indexing PDFs, was produced, and is presented here. The ANIE program is more accurate and faster than the manual graphical determination of Miller–Bravais indices, as it allows control of the exact error used in the calculation and removal of human error from the process.